Hide and peek : on the farm - Hambleton, Laura (Artist) (London, Pat-a-Cake, 2021)
With new farm friends to meet, colours to name, things to spot and lots to count, this peek-through book is perfect to share with little ones. Toddlers are learning new things all the time, and these bright books with peek-through pages are perfect for introducing colours and counting in a fun way. With a search-and-find game at the end and a hidden mouse to spot on every page, this book will have little ones coming back for more.